1994
DOI: 10.1126/science.7973633
|View full text |Cite
|
Sign up to set email alerts
|

SecA Homolog in Protein Transport Within Chloroplasts: Evidence for Endosymbiont-Derived Sorting

Abstract: The SecA protein is an essential, azide-sensitive component of the bacterial protein translocation machinery. A SecA protein homolog (CPSecA) now identified in pea chloroplasts was purified to homogeneity. CPSecA supported protein transport into thylakoids, the chloroplast internal membrane network, in an azide-sensitive fashion. Only one of three pathways for protein transport into thylakoids uses the CPSecA mechanism. The use of a bacteria-homologous mechanism in intrachloroplast protein transport provides e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(141 citation statements)
references
References 32 publications
5
136
0
Order By: Relevance
“…Immunoblots with horseradish peroxidase-conjugated 2°an-tibody (Bio-Rad) were developed with the ECL (Amersham) procedure according to the manufacturer's guidelines. The following sources and dilutions of primary antibodies were used: anti-Rbcs, 1:7,000 (E. Tobin, University of California, Los Angeles); anti-LHCP, 1:20,000 (Payan and Cline, 1991); anti-SecA, 1:5,000 (Yuan et al, 1994); anti-Pftf, 1:10,000 (Hugueney et al, 1995); anti-OE23, 1:20,000 (Fincher et al, 1998); anti-Hsp70, 1:5,000 (Yuan et al, 1993); anti-cpSRP54, 1:10,000 (R. Henry and K. Cline, unpublished results), anti-Toc75, anti-Toc34, and anti-Tic110, all at 1:7,000 (D. Schnell, Rutgers University, Newark, NJ).…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblots with horseradish peroxidase-conjugated 2°an-tibody (Bio-Rad) were developed with the ECL (Amersham) procedure according to the manufacturer's guidelines. The following sources and dilutions of primary antibodies were used: anti-Rbcs, 1:7,000 (E. Tobin, University of California, Los Angeles); anti-LHCP, 1:20,000 (Payan and Cline, 1991); anti-SecA, 1:5,000 (Yuan et al, 1994); anti-Pftf, 1:10,000 (Hugueney et al, 1995); anti-OE23, 1:20,000 (Fincher et al, 1998); anti-Hsp70, 1:5,000 (Yuan et al, 1993); anti-cpSRP54, 1:10,000 (R. Henry and K. Cline, unpublished results), anti-Toc75, anti-Toc34, and anti-Tic110, all at 1:7,000 (D. Schnell, Rutgers University, Newark, NJ).…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%
“…OE33 is routed into the thylakoid lumen on the thylakoid Sec pathway in chloroplasts (Yuan et al, 1994) by a bipartite signal peptide consisting of a stroma-targeting and lumen-targeting domain that is cleaved in two steps in a similar fashion as the ⌬pH pathway signal peptide. Following import and fractionation of OE33 in chromoplasts, processed mOE33 was recovered in the membrane subfrac- Figure 5.…”
Section: Isolated Chromoplasts Exhibit Plastid and Subplastid Proteinmentioning
confidence: 99%
“…Transthylakoid translocation mechanisms that have so far been identified are believed to each be specific for a subset of lumenal nuclear-encoded proteins. The isolation and characterization of chloroplastic homologues of bacterial SecA Yuan et al, 1994) has conclusively shown that one of these mechanisms is related to the bacterial Sec system. This translocation system is primarily responsible for the transport into the lumen of, among other proteins, plastocyanin (PC) and the 33-kDa subunit of the oxygen-evolving complex (OE33).…”
Section: Introductionmentioning
confidence: 99%
“…This translocation system is primarily responsible for the transport into the lumen of, among other proteins, plastocyanin (PC) and the 33-kDa subunit of the oxygen-evolving complex (OE33). Translocation via this pathway requires both nucleoside triphosphates and the chloroplastic SecA (Yuan et al, 1994). A transthylakoidal ApH is not required for this process but has been shown to stimulate the rate of translocation (Cline et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These routes include the spontaneous insertion of proteins (18), and signal recognition particle-dependent (9), ⌬pH-dependent (6, 21), and SecA-dependent pathways (22,33). A twin-arginine motif is specifically recognized by components of the ⌬pH-dependent pathway, and hydrophobic sequences are favored by the signal recognition particle-dependent pathway (12,13).…”
mentioning
confidence: 99%